Prognostic Impact of Weight Change During Adjuvant Chemotherapy in Patients With High-Risk Early Breast Cancer: Results From the ADEBAR Study - Mutschler, Nikola S.; Scholz, Christoph; Friedl, Thomas W. P.; Zwingers, Thomas; Fasching, Peter; Beckmann, Matthias; Fehm, Tanja; Mohrmann, Svjetlana; Salmen, Jessica; Ziegler, Carola; Jaeger, Bernadette; Widschwendter, Peter; et al. (Clinical Breast Cancer, 2018)
In addition to established prognostic factors, individual lifestyle-associated factors, such as obesity, physical activity, and diet, seem to modulate the course of breast cancer. The aim of this analysis was to evaluate the influence of weight changes during adjuvant chemotherapy on outcome in a large multicenter prospectively randomized trial.The ADEBAR trial compares a sequential chemotherapy consisting of epirubicin/cyclophosphamide followed by docetaxel to an epirubicin/5-fluorouracil/cyclophosphamide regimen in patients with lymph node-positive early breast cancer. Body weight was measured before each cycle of chemotherapy. According to the relative weight change (>= 5%) between the first and the last cycle, patients were categorized into the weight gain, weight loss, or stable weight group. Overall survival (OS) and disease-free survival were assessed by univariate Kaplan-Meier and multivariate Cox regression analyses.Concise data from 1080 of 1493 participants who completed all cycles of chemotherapy were available for analysis. Of 307 patients (24.8%) whose weight changed by >= 5%, 120 patients (11.1%) lost and 187 (17.3%) gained weight. Multivariate analysis showed a significant independent effect of weight change on OS (P = .039), but not on disease-free survival (P = .111). Both weight change groups had a worse OS compared to patients with stable weight (weight gain: hazard ratio, 1.55; 95% confidence interval, 1.01-2.40; P = .047; weight loss: hazard ratio, 1.55; 95% CI, 0.97-2.47; P = .067).Weight change of > 5% during adjuvant chemotherapy in patients with high-risk early breast cancer is associated with poor OS.
EVALuna2:56149